PENGAJARAN MENYIMAK BAHASA INGGRIS: MASALAH DAN SOLUSINYA - Adnan, Aryuliva (English Department FBS UNP, 2012)
For along time language teachers tend to ignore teaching listening. Among the four skills (listening, speaking, reading and writing) that are recognized as the keys to ‘knowing’ the language, listening is probably the least important to be taught. Actually speaking and listening are always interrelated. However listening is the most underdeveloped skill. In Indonesia the teachers tend to ignore to teach this skill by skipping it eventhough it is clearly stated in curriculum. Many reasons are mentioned by the teachers for not teaching listening, such as lack of teaching material, lack of school facilities, the speakers in the recorded material speak too fast, the students do not understand the vocabularies and the sentences used by the speakers. Basically, they realized that listening cannot be separated from other language skills like speaking, reading and writing. Listening is important since students may receive much of their information of their school through listening to instructors and to another. Listening has been regarded as the most frequently used language skills in the classroom. Besides, listening skill is important in the workplace, the family and the community. Furthermore nowadays listening skill is included in national examination for the level of Senior High School. The teachers then have no reasons to ignore and skip teaching listening, for they can vary their teaching materials, tasks, techniques and activities. Kinds of authentic materials can be taken from many recources, and kinds of activities to support teaching listening in the classroom can be done as well. Key words: teaching listening, listening materials, listening activities